Provision of health promotion programmes to people with serious mental illness: a mapping exercise of four South London boroughs. Issue 2 (15th May 2013) - O'Brien, C.; Gardner‐Sood, P.; Corlett, S. K.; Ismail, K.; Smith, S.; Atakan, Z.; Greenwood, K.; Joseph, C.; Gaughran, F.
<x xml:space="preserve">Abstract</x> Accessible summary Background: People with serious mental illness (SMI) are at increased risk of developing various physical health diseases, contributing to significantly reduced life expectancies compared with the general population. In light of this, the Department of Health have set the physical health of people with mental health problems as a priority for improvement. Additionally, the UK government encourages the NHS and local authorities to develop health promotion programmes (HPPs) for people with SMI. Aims: To document how many and what types of HPPs were available to people with SMI across four South London boroughs, UK. Results: We found 145 HPPs were available to people with SMI across the four boroughs, but with an inequitable distribution. We also found that certain HPPs set admission criteria that were likely to act as a barrier to improving health. Conclusions: A more integrated approach of documenting and providing information regarding the provision of HPPs for or inclusive of people with SMI is needed. Abstract People with serious mental illness (SMI) such as schizophrenia, schizoaffective disorders and bipolar disorder are at increased risk of developing diabetes, cardiovascular disease and respiratory disease, contributing to significantly reduced life expectancies. As a result, emphasis has been placed on developing Health Promotion Programmes (HPPs) to modify the risk of poor physical health in SMI. We examined how many and what types of HPPs are available for or inclusive of people with SMI across four borough in South London, UK. A cross‐sectional mapping study was carried out to identify the number of HPPs available to people with SMI. We found 145 HPPs available to people with SMI existed across the four boroughs but with an inequitable distribution, which in some boroughs we anticipate may not meet need. In some cases, HPPs set admission conditions which were likely to further impede access. We recommend that accurate and readily available information on the provision of HPPs for or inclusive of people with SMI is needed.